THE COURSE OF DESCENDING NECROTIZING MEDIASTINITIS DEPENDING ON THE ETIOLOGY OF THE DISEASE - Sheiko, V.D.; Ohanezian, A.H.; Dolzhkovyi, S.V.; Nebaba, S.V.; Cherkun, O.Yu.; Kryzhanovskyi, O.A.; Kaliuzhka, A.C. (World of Medicine and Biology, 2023)
Descending necrotizing mediastinitis is a rare complication of an oropharyngeal infection accompanied by phlegmon of the neck. The results of surgical treatment were analyzed depending on the etiology and dissemination of mediastinitis in order to improve the results of treatment of these patients. The treatment approach and course of the disease were studied in 27 patients with descending necrotizing mediastinitis, there were 22 men (81.5 %), 5 women (18.5 %); the mean age of patients was 48 years old (from 24 up to 71 years). Patients were divided into four groups: with parapharyngeal, odontogenic genesis, with perforations of the esophagus by foreign bodies and osteomyelitis of bones in the neck. Oropharyngeal infection was dominant amount etiological factors of descending necrotizing mediastinitis. It has been found that early patient seeking medical help and outpatient prescription of antibiotics improves treatment results; odontogenic mediastinitis is accompanied by the most severe course and high mortality; surgical treatment does not depend on the etiology of the disease, but understanding the ways of the infection dissemination may optimize surgical interventions and prevent the dissemination of the process in the mediastinum.